2013
DOI: 10.3390/ijerph10127310
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Splenocyte Apoptosis and Alterations of Bax, Bcl-2 and Caspase-3 mRNA Expression, and Oxidative Stress Induced by Dietary Nickel Chloride in Broilers

Abstract: Two hundred and forty avian broilers were equally divided into four groups, and raised with a corn-soybean basal diet or the same diet supplemented with 300, 600, 900 mg/kg NiCl2 for 42 days. Numbers or percentages of apoptotic splenocytes by flow cytometry (FCM) and TUNEL were higher (p < 0.05 or p < 0.01) in the 300, 600 and 900 mg/kg groups than those in the control group. Results measured by qRT-PCR and ELISA showed that mRNA expression and contents were significantly higher (p < 0.05 or p < 0.01) in Bax a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 66 publications
4
30
1
Order By: Relevance
“…In contrast to the aforementioned results, Cd oral administration produced peroxidative damage in chickens, as indicated by increase in TBARS, reduction in GSH concentration in liver and kidney, but increased CAT and SOD activities were observed in erythrocytes [144]. Dietary nickel chloride is also shown to have a negative effect on SOD and other antioxidant enzymes (GSH-Px and CAT) in the intestine [145], cecal tonsil [146] or splenocytes [147]. Similarly, vanadium inhibited SOD activity in chicken liver and kidney [148].…”
Section: Toxicological Stressescontrasting
confidence: 39%
“…In contrast to the aforementioned results, Cd oral administration produced peroxidative damage in chickens, as indicated by increase in TBARS, reduction in GSH concentration in liver and kidney, but increased CAT and SOD activities were observed in erythrocytes [144]. Dietary nickel chloride is also shown to have a negative effect on SOD and other antioxidant enzymes (GSH-Px and CAT) in the intestine [145], cecal tonsil [146] or splenocytes [147]. Similarly, vanadium inhibited SOD activity in chicken liver and kidney [148].…”
Section: Toxicological Stressescontrasting
confidence: 39%
“…Chen et al [17] have reported that NiCl 2 could induce oxidative toxicity in human lymphocytes. Our previous studies have also shown that dietary NiCl 2 in excess of 300 mg/kg causes splenic, intestinal, cecal tonsil, renal, and thymic oxidative damage and/or lesions [18][19][20][21][22]. It is also showed that NiCl 2 in excess of 300 mg/kg causes serum oxidative stress in broilers in our previous study [23].…”
Section: Introductionmentioning
confidence: 66%
“…As the first line of cellular defence against oxidative damage, SOD and CAT play an important role in these enzymatic mechanisms [26]. SOD can break up ROS and repair cellular damage caused by ROS [16]. CAT is responsible for the breakdown of hydrogen peroxide (H 2 O 2 ) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Living organisms possess several antioxidative agents (including enzymes such as SOD, GSH-Px, and CAT, Data are presented with the mean ± standard deviation (n = 5). GSH, and the ability to inhibit hydroxyl radical, and nonenzymatic antioxidants such as extra calcium and vitamin E) and protect them against the harmful effect of oxidative stress [16] [21] [22]. These antioxidants inhibit overproduced free radicals (including ROS and .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation